The views of adults with Huntington's disease on assisted dying: A qualitative exploration. (April 2018) - Regan, Laurence; Preston, Nancy J; Eccles, Fiona J R; Simpson, Jane
Background: Assisted dying is frequently debated publicly and research often includes the views of health professionals on this issue. However, the views of people with life-limiting conditions, for whom this issue is likely to have a different resonance, are less well represented. Aim: The purpose of this study was to explore the views of people who live with the inevitability of developing Huntington's disease, a genetically transmitted disease which significantly limits life, on assisted dying. Design: Using thematic analysis methodology, individual semi-structured interviews were conducted. Setting/participants: Seven participants (five women and two men) who were gene positive for Huntington's disease took part in the study. Results: Four themes were extracted: (1) autonomy and kindness in assisted dying: the importance of moral principles; (2) Huntington's disease threatens life and emphasises issues relating to death; (3) dilemmas in decision-making on assisted dying: "There are no winners" and (4) the absence of explicit discussion on dying and Huntington's disease: "Elephants in the room". Conclusions: Our findings suggest that talking to patients about assisted death may not cause harm and may even be invited by many patients with Huntington's disease. The perspectives of those who live with Huntington's disease, especially given its extended effects within families, add significant clinical and theoretical insights.